Predicting pain outcomes after traumatic musculoskeletal injury. Issue 8 (August 2016) - Rosenbloom, Brittany N.; Katz, Joel; Chin, Kelly Y.W.; Haslam, Lynn; Canzian, Sonya; Kreder, Hans J.; McCartney, Colin J.L.
Abstract : Abstract: Traumatic musculoskeletal injury results in a high incidence of chronic pain; however, there is little evidence about the nature, quality, and severity of the pain. This study uses a prospective, observational, longitudinal design to (1) examine neuropathic pain symptoms, pain severity, pain interference, and pain management at hospital admission and 4 months after traumatic musculoskeletal injury (n = 205), and (2) to identify predictors of group membership for patients with differing moderate-to-severe putative neuropathic pain trajectories. Data were collected on mechanism of injury, injury severity, pain (intensity, interference, neuropathic quality), anxiety (anxiety sensitivity, general anxiety, pain catastrophizing, pain anxiety), depression, and posttraumatic stress while patients were in-hospital and 4 months after injury. A third of patients had chronic moderate-to-severe neuropathic pain 4 months after injury. Specifically, 11% of patients developed moderate-to-severe pain by 4 months and 21% had symptoms immediately after injury that persisted over time. Significant predictors of the development and maintenance of moderate-to-severe neuropathic pain included high levels of general anxiety while in-hospital immediately after injury ( P < 0.001) and symptoms of posttraumatic stress 4 months after injury ( P < 0.001). Few patients had adequate pharmacological, physical, or psychological pain management in-hospital and at 4 months. Future research is needed among trauma patients to better understand the development of chronic pain and to determine the best treatment approaches. Abstract : General anxiety immediately after traumatic musculoskeletal injury and symptoms of posttraumatic stress 4 months after injury are associated with the development of moderate-to-severe neuropathic pain.